2021
DOI: 10.3390/brainsci11020264
|View full text |Cite
|
Sign up to set email alerts
|

Self-Positivity or Self-Negativity as a Function of the Medial Prefrontal Cortex

Abstract: Self and emotions are key motivational factors of a person strivings for health and well-being. Understanding neural mechanisms supporting the relationship between these factors bear far-reaching implications for mental health disorders. Recent work indicates a substantial overlap between self-relevant and emotion information processing and has proposed the medial prefrontal cortex (MPFC) as one shared neural signature. However, the precise cognitive and neural mechanisms represented by the MPFC in investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 78 publications
0
19
0
Order By: Relevance
“…We employed fMRI data sets from a previously reported study where healthy young adults performed two associative matching tasks using personal and emotion associations (Yankouskaya & Sui, 2021, Study 1). In the personal task, participants learned associations between simple geometrical shapes (e.g.…”
Section: Data Sets and Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…We employed fMRI data sets from a previously reported study where healthy young adults performed two associative matching tasks using personal and emotion associations (Yankouskaya & Sui, 2021, Study 1). In the personal task, participants learned associations between simple geometrical shapes (e.g.…”
Section: Data Sets and Tasksmentioning
confidence: 99%
“…A large body of research, including our previous work, reported overlapped neural substrates for emotion-prioritization effect and SPE (Kim et al, 2016;Smith et al, 2018). In particular, the effects of positive emotion resemble those triggered by self-relatedness (Yankouskaya & Sui, 2021). Most of the work used a seed-to-voxel connectivity analysis with the MPFC as a seed commonly reported in both self-referential and emotion processing.…”
Section: The Uniqueness Of Topological Cluster For the Spementioning
confidence: 99%
“…In behavioral studies, the same procedure has been also used with bodily stimuli such as faces and avatar bodies, yielding similar effects (Mattan, Quinn, Apperly, Sui, & Rotshtein, 2015 ; Payne, Tsakiris, & Maister, 2017 ; Woźniak & Hohwy, 2020 ; Woźniak & Knoblich, 2019 ). At the neural level, several previous experiments investigated which brain areas are affected by creating such arbitrary self‐associations for abstract, symbolic stimuli (Lockwood et al, 2018 ; Sui et al, 2013 ; Sui, Liu, Mevorach, & Humphreys, 2015 ; Yankouskaya et al, 2017 ; Yankouskaya & Sui, 2021 ; Yin et al, 2021 ; Zhao, Uono, Li, Yoshimura, & Toichi, 2018 ) and found that midline cortical structures (especially the ventromedial prefrontal cortex) are critically involved in such tasks. However, to date, no neuroimaging study used this approach to investigate which brain areas represent bodily, rather than abstract, information associated with the self.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanisms of the self-prioritisation effect and the positivity bias are still debated. One possibility is that the two biases are underpinned by the same neural substrate, the medial prefrontal cortex [25]. A combined self-positivity bias can be tested using a shape-label matching task which distinguishes between "good" and "bad" in addition to "self" and "other" [26].…”
Section: Introductionmentioning
confidence: 99%